The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1526602818781353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Revised Nellix Instructions for Use on Outcomes After Endovascular Aneurysm Sealing

Abstract: The IFU 2016 reduced the anatomic applicability to 34% from 75% for the original IFU 2013. The lack of significant intergroup differences in terms of survival and reinterventions suggests a limited effectiveness of the new IFU 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…It is important to bear in mind that the number of patients treated within the revised IFU was small (18.4%) as the majority of infrarenal cases were undertaken before the IFU revision. This observation reflects that reported in another large series by Zerwes et al 18 Compliance with the original (2013) IFU did show significantly lower incidence of type IA endoleak, ARM, and ACM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is important to bear in mind that the number of patients treated within the revised IFU was small (18.4%) as the majority of infrarenal cases were undertaken before the IFU revision. This observation reflects that reported in another large series by Zerwes et al 18 Compliance with the original (2013) IFU did show significantly lower incidence of type IA endoleak, ARM, and ACM.…”
Section: Discussionsupporting
confidence: 90%
“…There are few published data reporting outcomes with respect to the revised IFU; however, it is apparent that the morphologic applicability was significantly reduced. 18 This study reports the midterm outcomes of a large cohort of patients having undergone EVAS at a single large-volume aortic center.…”
mentioning
confidence: 99%
“…In the current study, preoperative aortic neck diameter, neck length, and diameter ratio were preoperative predictors of migration, any endoleak, and aneurysm growth after EVAS. Moreover, despite IFU refinement, more than a quarter of patients had complications over time, an observation similar to that recently reported by Zerwes et al 8 Previous studies 9,10 demonstrated caudal and lateral displacement of the EVAS endosystem, which might be due to the instability of intraluminal thrombus within the aneurysm sac. A larger ratio between the maximum AAA and lumen diameters might reflect the potential for this instability to adversely affect the endobags and stent frames, especially in patients with large sac thrombus volumes.…”
Section: Discussionsupporting
confidence: 83%
“…127 Indeed, anatomical constraints limit its applicability and outsideof-instructions for use greatly increases the risk of device failure. 128,129 Thus, improvements in the technique and longer follow-up are necessary before it can be implemented on a large scale and its adoption with the sole purpose of reducing the rate of T2EL is not justified by current evidence. 130 Also, whether the best stent graft to prevent T2EL would combine the polymer sacs from Nellix with a conventional stent graft that uses self-expanding covered stents that generate radial force for adequate proximal sealing remains a topic to investigate.…”
Section: Preventionmentioning
confidence: 99%